KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS COVID-19 AMONG NURSING STUDENTS DURING PANDEMIC - Lani Natalia Watania; Eva Gultom; Chriska Sinaga (Universitas Pelita Harapan, 2021)
As the future of health care providers, nursing students need to have the quality of knowledge and respond to rapid changes in every situation such as in the COVID-19 pandemic, in which these students' condition reflects the readiness of nursing students to face the increasing cases in the country. The purpose of this study was to evaluate the level of knowledge, attitude, and practice among nursing students in a private university during the pandemic. This research applied a descriptive quantitative design. A total sampling technique was conducted. The sample of this study was 290 nursing students who had experience in the clinical practice and agreed to participate in the study. The instrument consisted of 53 survey questions that have been adapted and modified from World Health Organization guidelines related to COVID-19. Data collection was carried out in November 2020, using a self-administered online questionnaire. A univariate analysis was used to analyze the variables using frequency distribution. This study revealed that students’ knowledge about COVID-19 was 55.9% in high level, the student's attitude towards COVID-19 reported 63.8% in moderate level and 79% of the students practice moderately in preventing COVID-19 during the pandemic. Therefore, there is a need to provide a follow-up program to support the knowledge, attitude, and practice of nursing students during the pandemic.